Fifty key thinkers on globalization - Coleman, William D. 1950- (Routledge, 2013)
"Fifty Key Thinkers on Globalization is an outstanding guide to often-encountered thinkers whose ideas have shaped, defined and influenced this new and rapidly growing field. The authors clearly and lucidly survey the life, work and impact of 50 of the most important theorists of globalization including: - Manuel Castells - Amartya Sen - Zygmunt Bauman - Jan Aart Scholte Each thinker's contribution to the field is evaluated and assessed, and each entry includes a helpful guide to further reading. Fully cross-referenced throughout, this remarkable reference guide is essential reading for students of politics and international relations, economics, sociology, history, anthropology and literary studies. William Coleman is Professor of Political Science at McMaster University, Canada. He has published widely in the areas of globalization studies and global public policy. Alina Sajed is a Lecturer at McMaster University, Canada"--
Includes bibliographical references and index. - Print version record
Keywords: Globalization; Globalization -- Social aspects; Mondialisation; Mondialisation; Aspect social; globalism; POLITICAL SCIENCE; General; POLITICAL SCIENCE; Globalization; SOCIAL SCIENCE; Sociology; General; Globalization; Social aspects